In vitro toxicity evaluation of graphene oxide on A549 cells - Chang, Yanli; Yang, Sheng-Tao; Liu, Jia-Hui; Dong, Erya; Wang, Yanwen; Cao, Aoneng; Liu, Yuanfang; Wang, Haifang (Toxicology letters, 2011)
Graphene and its derivatives have attracted great research interest for their potential applications in electronics, energy, materials and biomedical areas. However, little information of their toxicity and biocompatibility is available. Herein, we performed a comprehensive study on the toxicity of graphene oxide (GO) by examining the influences of GO on the morphology, viability, mortality and membrane integrity of A549 cells. The results suggest that GO does not enter A549 cell and has no obvious cytotoxicity. But GO can cause a dose-dependent oxidative stress in cell and induce a slight loss of cell viability at high concentration. These effects are dose and size related, and should be considered in the development of bio-applications of GO. Overall, GO is a pretty safe material at cellular level, which is confirmed by the favorable cell growth on GO film.